2011
DOI: 10.1093/deafed/enr016
|View full text |Cite
|
Sign up to set email alerts
|

Personal Factors That Influence Deaf College Students' Academic Success

Abstract: Research tells us that academic preparation is key to deaf students' success at college. Yet, that is not the whole story. Many academically prepared students drop out during their first year. This study identified entering deaf college students' personal factors as assessed by their individual responses to both the Noel-Levitz College Student Inventory Form B and the Learning and Study Strategies Inventory, second edition (LASSI). Entering students in 3 successive cohorts (total n =437) participated in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 6 publications
3
39
0
Order By: Relevance
“…English and Math were chosen as competent subjects by the normal hearing group indicating that our SDHH were behind their peers in these subjects. This is in line with other studies who also found the English and Math levels of SDHH to be behind that of their peers [51].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…English and Math were chosen as competent subjects by the normal hearing group indicating that our SDHH were behind their peers in these subjects. This is in line with other studies who also found the English and Math levels of SDHH to be behind that of their peers [51].…”
Section: Discussionsupporting
confidence: 93%
“…Most of the hearing students in this study were truthful in their abilities at school, However most of the SDHH in this study said their performance was excellent and none of them reported average or below average performances, these overestimated performances are also in line with another study that found that students whose grade point average (GPA) placed them in lower ranges of performance overestimated their own academic performance and those whose GPA placed them in a higher range were more truthful with their performance [51].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The LASSI scale has been used different purpose and adapted for many other populations. For instance, deaf students' success at college level (Albertini, Kelly, & Matchett, 2012), at collage developmental students level (Deming, Valeri-Gold, & Idleman, 1994), African American at precollege students level (Flowers, Bridges, & Moore, 2012), university students' academic achievement (Taheri et al, 2017), Chinese version of the Learning and Study Strategies Inventory (Yip, 2013), Qatar; at university student level (Alkhateeb & Nasser, 2014). In the early developmental stage of LASSI, 19 general categories were determined from survey of published study skills materials.…”
Section: Assessing Learning Strategies: Lassimentioning
confidence: 99%